Understanding the importance of motivational intensity in English as a foreign language context: A structural equation modeling analysis - Wang, Cong; Zhu, Sida; Zhang, Haijing (Frontiers in Psychology, 2022)
Motivational intensity is the effort learners make in language learning. It is an essential component and a direct measurement of L2 motivation. Few studies have distinguished motivational intensity from motivation and explored its role in learning English as a foreign language. This study examined 208 university students from Hong Kong to investigate the factors that affect motivational intensity and explored the relationship between motivational intensity and learning motivation using structural equation modeling. The students’ motivational intensity was affected by personal factors (daily English-learning time and stage of English learning), family factors (monthly household income and parental attitudes), and school factors (English learning engagement and satisfaction). The differences in personal factors, school factors and monthly household income of family factors among different motivational intensity groups were significant whereas the difference in parental attitudes (family factors) between the high- and the low-motivational intensity groups was insignificant. As for the relationship between motivational intensity and motivation, motivational intensity indirectly affected students’ intrinsic interest through their attitudes towards native English speakers (β=0.16, p=0.041<0.05). The significant path coefficient from the learning situation to attitudes towards native speakers was negative (p<0.05), indicating that attitudes towards native speakers decline even when the learning situation improves. This study enriched the theoretical study of motivation theory and provided teaching suggestions for improving EFL learning.